Antioxidant potential of low molecular weight fucoidans from Sargassum autumnale against H2O2-induced oxidative stress in vitro and in zebrafish models based on molecular weight changes. (1st August 2022) - Geun Lee, Hyo; Jayawardena, Thilina U.; Liyanage, N.M.; Song, Kyung-Mo; Choi, Yun-Sang; Jeon, You-Jin; Kang, Min-Cheol
Highlights: Low molecular weight fucoidans from Sargassum autumnale were investigated. The protamex-assisted hydrolysate fraction protected against oxidative stress. The fraction was structurally and physically similar to commercial fucoidan. The fraction was rich in fucose and galactose. This fucoidan may be an alternative to antioxidant agents in functional foods. Abstract: In this study, we investigated the potential antioxidant abilities of low-molecular weight fucoidans from enzyme-assisted hydrolysates of Sargassum autumnale, based on molecular weight changes, in vitro and in vivo . The yield and free radical-scavenging activities of enzyme-assisted hydrolysates of S. autumnale were screened. The protamex-assisted hydrolysate of S. autumnale (SAP) presented the highest yield and 2, 2-diphenyl-1-picrylhydrazyl (DPPH)-scavenging activity; therefore, it was chosen for fucoidan purification. Three fucoidan fractions were observed in SAP, and their antioxidant activity was assessed. Fucoidan fraction 3 of protamex-assisted hydrolysate of S. autumnale (SAPF3) offered significant protection against H2 O2 -induced oxidative stress, and was structurally and physically similar to commercial fucoidan. Fucose and low-molecular weight fucoidans were highly concentrated in SAPF3. The results of our study show that SAPF3, a low-molecular weight fucoidan from S. autumnale, possesses strong antioxidant properties and may be an effective alternative to antioxidant agents in the functional food industry.